2022
DOI: 10.3390/membranes12010068
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Micro-Computed Tomography: A Powerful Device to Analyze the 3D Microstructure of Anode-Electrolyte in BaZr0.8Y0.2O3 Protonic Ceramic Electrochemical Cells and the Reduction Behavior

Abstract: New advanced fuel cell technologies are moving towards high-temperature proton conductors (HTPCs) to meet environmental issues. Their elaboration remains a challenge and micro-computed tomography (µCT) is an innovative way to control their quality. NiO-BZY anodic supports of a protonic ceramic electrochemical cell (PCEC), elaborated by co-tape casting and co-sintered at 1350 °C, were coated with a BZY20 electrolyte layer by DC magnetron sputtering. The µCT allowed to observe defects inside the volume of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…8 Y 0 . 2 (purity 99.9%, Ø 50 mm × 6 mm) targets as described in previous work [56]. The reactor is a 90 L cylinder Alcatel 604 SCM (CIT Alcatel, Annecy, France) pumped down via a turbomolecular pump system that permitted a residual vacuum below 10 −4 Pa.…”
Section: Elaboration Processmentioning
confidence: 99%
“…8 Y 0 . 2 (purity 99.9%, Ø 50 mm × 6 mm) targets as described in previous work [56]. The reactor is a 90 L cylinder Alcatel 604 SCM (CIT Alcatel, Annecy, France) pumped down via a turbomolecular pump system that permitted a residual vacuum below 10 −4 Pa.…”
Section: Elaboration Processmentioning
confidence: 99%
“…As a result of this Special Issue proposal, five research papers [12][13][14][15][16] from four different countries have been published. Researchers at academic institutions and the French National Centre for Scientific Research (CNRS) from France [12,13,15], Mexico [15], Germany [14], and Taiwan [16] contributed to this work. It is important to point out that the research reported in Ref.…”
mentioning
confidence: 99%
“…Moreover, all the published papers reported experiments performed on electrolyzers that demonstrate the relevance of the papers and the significance of using experimental data for investigation purposes. Hence, the published papers reported on new contributions compared to the current literature, including an investigation of the effects of current ripple from power electronics on the performance of PEM electrolyzers [12]; the use of X-ray micro-computed tomography to examine the 3D microstructure of the anode-electrolytes of electrolyzers [13]; the development of a mathematical model to evaluate the cell polarization, current density distribution and water flow paths inside a cell under low stoichiometry conditions [14]; the analysis of the decrease in the open-circuit voltage of the PEM electrolyzer during shutdown operation and its modeling [15]; and the application of micro-electro-mechanical systems to monitor, in real-time, the state-of-health of a PEM electrolyzer [16].…”
mentioning
confidence: 99%